2017
DOI: 10.1097/pec.0000000000000607
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the GlideScope Cobalt® and Storz DCI® Video Laryngoscopes in Children Younger Than 2 Years of Age During Manual In-Line Stabilization

Abstract: Trainees were able to safely perform tracheal intubation in children younger than 2 years using any of the studied laryngoscopes, although Storz use resulted in a longer TTSI when compared to direct laryngoscopy. Video laryngoscopy may enhance best Cormack-Lehane glottic view during manual in-line cervical spine immobilization, but additional technical skills are needed to successfully complete tracheal intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
0
21
0
1
Order By: Relevance
“…This literature reports improved glottic views for children undergoing elective surgery, but there is often equivalent or in some cases longer times to intubation. [13][14][15][16] A meta-analysis of pediatric VL studies found improved laryngeal views, but no difference in FPS and no difference or increased time to intubation when VL were used by experienced anesthesiologists. 14 In our study, residents performed most of our intubations, similar to the National Emergency Airway Registry study, which reported that 83% of first attempts at 10 participating centers were completed by resident physicians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This literature reports improved glottic views for children undergoing elective surgery, but there is often equivalent or in some cases longer times to intubation. [13][14][15][16] A meta-analysis of pediatric VL studies found improved laryngeal views, but no difference in FPS and no difference or increased time to intubation when VL were used by experienced anesthesiologists. 14 In our study, residents performed most of our intubations, similar to the National Emergency Airway Registry study, which reported that 83% of first attempts at 10 participating centers were completed by resident physicians.…”
Section: Discussionmentioning
confidence: 99%
“…12,[20][21][22] Most of the anesthesia literature on elective intubations has shown no improvement in FPS with the use of VL and increased intubation times. [13][14][15][16] The very limited literature in emergency medicine (EM) has also revealed no difference in FPS or adverse events with VL compared with DL. 20,21 We reviewed our data over the past 10 years to see if there was an increase in FPS-AE associated with VL use in our pediatric ED.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Einige SR deuten auf ein erhöhtes Risiko einer verlängerten Intubationszeit und einer erfolglosen Intubation mit Videolaryngoskopie hin [192][193][194]. Neuere RCT-und Beobachtungsstudien deuten auf einen Vorteil hin, aber die Evidenzen bleiben widersprüchlich [195][196][197][198][199][200][201][202] [203]. Bei kleinen Kindern kann die Inzidenz von Rhythmusstörungen verringert werden, wenn Atropin zusätzlich zu den für die Notfallintubation verwendeten Medikamenten gegeben wird [204].…”
Section: Videolaryngoskopieunclassified
“…Finally, Vadi et al [78] compared trainee intubation times obtained using the GlideScope Cobalt VL, the Storz DCI VL and DL in young children with immobilized cervical spines and concluded that VL "may enhance best Cormack-Lehane glottic view during manual in-line cervical spine immobilization, but additional technical skills are needed to successfully complete tracheal intubation" and that "obtaining a grade 1 Cormack-Lehane glottic view was less likely" with DL.…”
Section: Glidescope Use In Infants and Childrenmentioning
confidence: 99%